Kemampuan representasi matematis siswa dalam materi teorema pythagoras - Mardiani, Mardiani; Sugiatno, Sugiatno; Fitriawan, Dona; Halini, Halini; T, Ahmad Yani (IKIP Siliwangi, 2024)
This study aims to analyze the mathematical representation ability of SMA Negeri 1 Sungai Kakap students on Pythagorean theory material using visual, symbolic, and verbal strategies. The method used was quantitative descriptive with the research subjects of 36 students in class X. The collection method included questionnaires, reports, and documentation. The instruments used for data collection in this study are mathematical representation test questions and interviews. Data analysis techniques are carried out with quantitative data analysis techniques and descriptive analysis techniques. Based on the test results, it shows that students' mathematical representation skills need to be improved, with an achievement rate of 43% with a medium category. Students' visual representation ability was only 36%, while verbal and symbolic representation was much higher, at 42% and 50%, respectively. In general, students can answer the questions correctly, but there are errors in interpreting and translating the representation between visual, symbolic, and verbal. These findings point to the need for improved understanding and translation between different forms of mathematical representation to improve understanding of the concept of the Pythagorean theorem.